The Implementation Religious Characters in the Profiles of Pancasila Students through Religious Activities in Schools - Susanti, Atika; Darmansyah, Ady; Assenhaji, Salih Abdulrahman (Eduprof : Islamic Education Journal, 2023)
Religious character is a key aspect as it connects humans vertically with their God, which also impacts the horizontal relationship of humans with their environment. This research aims to describe The Implementation Religious Characters in the Profiles of Pancasila Students through Religious Activities in Schools. The research method used is a qualitative descriptive research design. The subject of this research is the teachers and students of SDIT Baitul Izzah in Bengkulu City. The research instruments used were observation guidelines, interviews and documentation. Research data collection techniques through observation, teacher interviews, and document analysis. Qualitative data analysis techniques using thematic analysis techniques. The results showed that school culture-based programs at Elementary School Baitul Izzah Bengkulu City, included routine activities such as (1) reading the Quran every morning, (2) memorizing the Quran and Asmaul Husna on Fridays, (3) performing congregational prayers (Duha, Zuhr, Asr, and Friday prayers), (4) organizing Bilal Iman Taqwa evenings, and (5) conducting the Islamic Personal Development (Bina Pribadi Islam) program on fiqh and creed every Friday. Through these programs, students have engaged in religious activities and practice religious values in their daily lives